Gender biases in the training methods of affective computing: Redesign and validation of the Self-Assessment Manikin in measuring emotions via audiovisual clips - Sainz-de-Baranda Andujar, Clara; Gutiérrez-Martín, Laura; Miranda-Calero, José Ángel; Blanco-Ruiz, Marian; López-Ongil, Celia (Frontiers in Psychology, 2022)
Audiovisual communication is greatly contributing to the emerging research field of affective computing. The use of audiovisual stimuli within immersive virtual reality environments is providing very intense emotional reactions, which provoke spontaneous physical and physiological changes that can be assimilated into real responses. In order to ensure high-quality recognition, the artificial intelligence (AI) system must be trained with adequate data sets, including not only those gathered by smart sensors but also the tags related to the elicited emotion. Currently, there are very few techniques available for the labelling of emotions. Among them, the Self-Assessment Manikin (SAM) devised by Lang is one of the most popular. This study shows experimentally that the graphic proposal for the original SAM labelling system, as devised by Lang, is not neutral to gender and contains gender biases in its design and representation. Therefore, a new graphic design has been proposed and tested according to the guidelines of expert judges. The results of the experiment show an overall improvement in the labelling of emotions in the pleasure–arousal–dominance (PAD) affective space and, particularly, for women. This research proves the relevance of applying the gender perspective in the validation of tools used throughout the years.